Morphological, magnetic and EPR studies of ZnO nanostructures doped and co-doped with Ni and Sr. Issue 20 (15th October 2021) - Peña-Garcia, R.; Guerra, Y.; Castro-Lopes, S.; Camejo, Y.M.; Soares, João M.; Franco, A.; Padrón-Hernández, E.; Cabrera-Baez, M.
Abstract: Herein, were analyzed the effects of Sr and Ni addition on the morphological, electronic and magnetic properties of ZnO nanoparticles synthesized by the sol gel route. Morphological analysis showed agglomerated particles with nonuniform shapes (polyhedral, hexagonal and spherical) and the average size distributions were calculated counting more than 100 nanoparticles (sizes between 43 and 75 nm). For pure ZnO sample, the selected area electron diffraction (SAED) showed bright and concentric discontinuous diffraction rings, while the co-doped samples, presented patterns well-organized concentric circular rings, typical of reflection of regularly arranged atoms. The electron paramagnetic resonance (EPR) was employed to analyze the intrinsic defects due to the dopant inclusion. In addition, the EPR spectra were simulated using the spin quantum number ( S = 1) for Ni 2+ to understand the experimental results. Ni ions were used as a local probe in the comparative study by EPR, capturing subtle modifications in the zero-field interactions due to induced strain in the lattice. Microscopically the changes observed, through the EPR study, result from the reduction of the axial distortion of the ligand field and increasing in the distortion perpendicular to the principal axis. Magnetic study showed a typical significant diamagnetism at 300 K, while a paramagnetic contribution was more evident at 4 K. The work contributes to clarify the complex magnetic response in ZnO nanoparticles doped and co-doped with Sr and Ni.